A formação contínua de professores de língua inglesa da rede municipal pública de ensino de Vitória, ES, à luz da análise de necessidades - Almeida, Christine Sant Anna de (2014)
The present research, a qualitative one, characterized as a case study (STAKE, 1995; YIN, 2010), aimed to identify the teacher education needs (SILVA, 2000; DI GIORGI et al., 2010; SANTANA, 2010) of the in-service English teachers from the public municipal schools of Vitória, ES, in order to examine to what extent the continuing education process offered by the institution meets the needs of those teachers. For that purpose, a needs analysis was conducted with the teachers (BARBIER; LESNE, 1977; HUTCHINSON; WATERS, 1987; DUDLEY-EVANS; ST. JOHN, 1998; RODRIGUES; ESTEVES, 1993; GALINDO; INFORSATO, 2008), making use of a questionnaire with the teachers and interviews with the managers. The results revealed that the continuing education process offered does not meet the needs of the teachers and motivated the elaboration, with the purpose of illustration, of a suggestive script of in-service education activities. The script meets the requirements and guidelines of governing documents (BRASIL, 1996a, 1998b, 1998c, 2002a; VITÓRIA, 2004a, 2004b, 2007), the scholars´ suggestions as desirable for the continuing education of teachers of English (BROWN, 2001; CELANI, 2001; KUMARAVADIVELU, 2011), as well as the needs expressed by the teachers